APLIKASI MODEL PENGAMBILAN KEPUTUSAN DALAM PERILAKU FERTILITAS - Ade Latifa (Research Centre for Population, Indonesian Institute of Sciences, 2010)
This paper focus on the decision making models which are initially applied in the economic, politic and psychology science. Only a few papers explore this issue, most of its reveal about the result study or the output instead of discussing the process of decision making. Discussion about the usage of decision making model as the analytic tool and the application of the model is quite few. Based on that, this paper try to explore the decision making process in relating to the fertility behavior by applying rational approach that was developed by Simon and Carley. Fertility behavior is important to analyze because as a variable, fertility contribute to the poverty condition in North Sulawesi border area (2006- 2007/ Therefore more deeply understanding about the decision making process related to the fertility matters, is necessary. Data based on the study of socio demographic poverty that was conducted by the PPK-LIPI in the North Sulawesi border area. Based on the decision making model it is indicated that the economic factor play an important role in the rationality of the fertility decision making.Keywords: Decision making model, rational approach, fertility behavior, North Sulawesi border area